PERANCANGAN PUREPLAY CUSTOMER JOURNEY DOKTER KANDUNGAN DALAM MENINGKATKAN VAKSINASI INFLUENZA IBU HAMIL (STUDI KASUS PT KSF) - Federal Marcos; Donant Alananto Iskandar (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2026)
This study aims to design a pureplay customer journey to improve influenza vaccination uptake among pregnant women by optimizing digital interactions with obstetricians. A descriptive qualitative approach was used, employing in-depth interviews, non-participant observations, and document analysis of digital communication activities. Data were analyzed through transcription, thematic coding, gap analysis, and customer journey mapping based on the RACE Framework (Reach, Act, Convert, and Engage). The findings indicate that the current digital journey is fragmented, lacks personalization, and is insufficient in supporting obstetricians’ clinical decision-making. This study proposes a more structured pureplay customer journey that emphasizes segmentation, content relevance, decision support, and continuous engagement. The proposed model is expected to enhance market adoption of influenza vaccination for pregnant women.